Isometrische Maximalkraftmessungen der Quadrizepsmuskulatur - Herbsleb, M.; Tutzschke, R.; Czepa, D.; Gabriel, H.H.W.; Hilberg, T. (Hämostaseologie, 2010)
The quadriceps femoris muscle (QF) plays an important role in locomotion. However, assessing the total number of attempts to evaluate the maximal isometric strength (Fmaxiso) regarding reliability and feasibility remain less characterised. Patients, methods: 28 patients with haemophilia (H) (26 severe, 2 moderate) and 27 healthy controls (C) matched for age (H: 44 ± 11, C: 42 ± 12) and anthropometric data were measured separately for the left and right leg for Fmaxiso of QF using m3 diagnos (SCHNELL®). We repeated the Fmaxiso measures after 48 h in 14 H and 13 C. Results: The system m3 diagnos showed strong reliability (ICC = 1.0; SEM = 0.0; CA = 1.0). H and C demonstrated significant differences in Fmaxiso (H r = 153 Nm, l = 164 Nm; K r= 289 Nm, l = 280 Nm; p ≤ 0.001). Additionally, H and C revealed significant differences between the 1st and 3rd to 6th attempts. No differences were observed between the 3rd, 4th, 5th and 6th attempts. Conclusion: Both groups showed high test-retest-reliability of Fmaxiso (ICC/SEM: H l = 0.98/7.1 r = 0.99/4.9; K l = 0.69/11.3 r = 0.95/5.8). Starting from the 3rd attempt, reliable measurements of the Fmaxiso in patients suffering from severe haemophilia are feasible.
Keywords: Haemophilia; quadriceps; isometric strength; reliability